On the Assembly of the League of nations 1930. Report of the Commission of the L.S.I. for problems of the League of nations to the executive of the Labour and socialist international at its meeting in Zurich, August 22-23, 1930 (Secretariat of the Labour and socialist international)
Problems of the League of nations.